Pinna nobilis in the south Marmara Islands (Sea of Marmara); it still remains uninfected by the epidemic and acts as egg laying substratum for an alien invader - CINAR, MELIH ERTAN; BİLECENOĞLU, MURAT and YOKEŞ, MEHMET BAKI and GÜÇLÜSOY, HARUN (Mediterranean Marine Science, 2021)
A total of 12 Pinna nobilis beds were found and studied at depths varying between 2 and 6 m in the south Marmara Islands (Sea of Marmara). Fan mussel individuals in the beds were healthy with a few old dead specimens, indicating that the epidemic, which has devastated P. nobilis populations in the Mediterranean Sea, has not reached the Sea of Marmara, making the region a refuge area for the species. The average density of P. nobilis in the area varied between 0.6 ind.10 m-2 and 24 ind.10 m-2. The P. nobilis shells overall provided substrata or refuge for 14 species (10 sessile and 4 motile organisms), from macroalgae to fish. Shells of juvenile and adult specimens had different species assemblages. Four distinct assemblages were detected on shells, primarily formed by the red alga Gracilaria bursa-postaris, egg cocoons of the invasive alien Rapana venosa, the gastropod Bittium reticulatum and the serpulid polychaete Spirobranchus polytrema.